1996
DOI: 10.1007/s002239900132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salmon Calcitonin on Femoral Bone Quality in Adult Ovariectomized Ewes

Abstract: The aim of this study was to evaluate the effect of intermittent calcitonin on femoral bone quality in adult ewes from the time of ovariectomy. Six months after the start of the experiment, bone density measurements and mechanical testing (torsion and resonant frequency analysis of the diaphysis and compression of an excised trabecular bone cylinder from the femoral neck) were performed in sham-control and ovariectomized (OVX) ewes treated with placebo or salmon calcitonin (50 or 100 units, 3 times/week). Crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 18 publications
3
27
0
2
Order By: Relevance
“…Since those reports, our group (Newman et al, 1995;Thorndike and Turner, 1999) and others (Pastoureau et al, 1989;Hornby et al, 1994;Atley, 1996;Geusens, 1996;O'Connell, 1999) have documented osteopenia in sheep following OVX as well as the response to various agents such as estradiol implants (Turner et al, 1995a,b;O'Connell, 1999), salmon calcitonin (Geusens et al, 1996), and the selective estrogen receptor modulator (SERM) raloxifene (Turner et al, 1999a). Our earlier findings showed a significant decline in cancellous bone volume (BV/TV%) of the iliac crest following OVX (Turner et al, 1993).…”
Section: Sheepmentioning
confidence: 71%
See 1 more Smart Citation
“…Since those reports, our group (Newman et al, 1995;Thorndike and Turner, 1999) and others (Pastoureau et al, 1989;Hornby et al, 1994;Atley, 1996;Geusens, 1996;O'Connell, 1999) have documented osteopenia in sheep following OVX as well as the response to various agents such as estradiol implants (Turner et al, 1995a,b;O'Connell, 1999), salmon calcitonin (Geusens et al, 1996), and the selective estrogen receptor modulator (SERM) raloxifene (Turner et al, 1999a). Our earlier findings showed a significant decline in cancellous bone volume (BV/TV%) of the iliac crest following OVX (Turner et al, 1993).…”
Section: Sheepmentioning
confidence: 71%
“…To evaluate the effect of salmon calcitonin on bone mass, compression (lumbar vertebrae and femoral neck), torsional stress (femoral neck only) and resonant frequency were measured in excised femoral neck and lumbar vertebral sam- Percentage change (mean + SE) in lumbar spine BMD after 6 months of treatment with estradiol implants (OVXE), and two doses of the SERM, raloxifene (see Turner et al, 1999a for details). Running title: Animal models -osteoporosis ples from OVX sheep (Geusens, 1992;Geusens, 1996). In that study, bone mass was measured using DXA and dualenergy quantitative computed tomography (DEQCT).…”
Section: Sheepmentioning
confidence: 99%
“…Recent research has demonstrated that the BMD of the vertebral body in ovariectomized sheep exhibits a significant downward trend after 1 year; however, no statistically significant difference was identified when compared with a sham-control group (18). It has been suggested that a short-term ovariectomized sheep model should be defined as an osteopenia model, rather than an osteoporosis model (29). Lill et al (12) hypothesized that >1 year was required to establish an osteoporosis model using an ovariectomy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Geusens et al (29) observed that at 6 months after an ovariectomy, bone mass in the femoral neck of sheep decreased by between 3 and 9%; however, no statistically significant difference was observed when compared with a (9,12) found that following application of an ovariectomy and restricted calcium intake, the BMD of the radius in sheep decreased by 5.5%. In the study by Turner et al (32), the BMD was shown to decrease by 3-8%.…”
Section: Johnson Et Almentioning
confidence: 99%
“…(24,25) We have shown that salmon calcitonin (sCT) preserved BMD measured by DXA and bone strength in trabecular bone of the femoral neck in sheep treated with sCT. (26) In postmenopausal women injected with sCT, the initial sCT study showed clinical efficacy. (27) It prevents trabecular bone loss when given immediately after menopause.…”
mentioning
confidence: 99%